Public Relations Strategy in Strengthening Brand Image at Alila Villas Uluwatu Bali - I Gusti Ayu Diah Tantri; Ni Made Ernawati; Ni Nyoman Sri Astuti (Politeknik Negeri Bali, 2020)
This research aims to formulate the most appropriate public relations strategy as an option in strengthening brand image that can apply by Alila Villas Uluwatu to take advantage of the opportunities and anticipate the existing threats by utilizing the strength and anticipate shortcomings. Thus, it can help to achieve the occupancy target. This research used sequential exploratory mixed methods; IE (Internal-External) Matrix, SWOT (Strengths Weaknesses Opportunities Threats) and QSPM (Quantitative Strategic Planning Matrix). This research used participation observation, semi-structured interview, questionnaires and documentation as data collecting methods. The study used a purposive sampling technic and the respondents consist of 7 people from the Sales & Marketing Department. The result of data analysis shows IFAS (Internal Factor Analysis Summary) score is 2.88 and EFAS (External Factor Analysis Summary) score is 2.80, which indicates the current position of public relations strategy is in cell V, which is of growth and stability in IE Matrix that requires horizontal integration. The SWOT analysis gives 7 alternative strategies, of which the highest TAS (Total Attractive Score) is 167.41 that generated by QSPM analysis. Thus, the main strategy that recommended which is the highest among the 7 of alternative strategies is allocating more budget to increase the number of hosted social influencers & media according to the target market and also for boosted branding contents on Facebook and Instagram.